Endometrial cancer cells can express fibrinogen: Immunohistochemistry and RT-PCR analysis. (2nd April 2016) - Uccella, S.; Cromi, A.; Vigetti, D.; Cimetti, L.; Deleonibus, S.; Casarin, J.; Passi, A.; Riva, C.; Ghezzi, F.
Abstract : We investigated whether endometrial cancer (EC) cells can express fibrinogen. Consecutive patients treated for EC were enrolled (cases). A control group of women who had hysterectomy for benign conditions was identified in a case:control ratio of 4:1. Immunohistochemistry and reverse transcription polymerase chain reaction (RT-PCR) were performed to identify the presence of fibrinogen and the mRNA of its three chains (α, β, γ) in the tissue specimens from both cases and controls. Sixteen EC cases and 4 benign controls were included. Immunohistochemistry failed in one case of EC. In 12/15 (80%) cases versus 0 controls, a moderate-to-intense positivity for fibrinogen was observed ( p = 0.09; OR: 32.1; 95%CI: 1.4–752.9). Six (37.5%) women among the cases versus 0 controls expressed RNA for at least one chain of fibrinogen ( p = 0.25). All the cases (6/6, 100%) with positive RT-PCR had moderate-to-intense positive immunohistochemistry. Molecular and immunohistochemistry show that some cases of EC have the capability to express fibrinogen and the mRNA of at least one of its chains.